Towards better-informed dispersal probabilities in historical biogeography: Arachnids as a model lineage - Kuntner, Matjaž; Turk, Eva (Frontiers in Arachnid Science, 2022)
Historical biogeography is an integrative scientific field critical for testing evolutionary hypotheses pertinent to organismal distributions, but despite recent theoretical and analytical advances, biogeographic reconstructions continue to struggle with accuracy and rigor. Most modern studies include the three elements needed for historical biogeographic inference, namely a time-calibrated phylogeny, contemporary taxonomic distributions, and estimations of organismal dispersal probabilities. The latter, we argue, are particularly vague, and historical biogeography would greatly benefit from dispersal probability estimations that are better informed and biologically meaningful. To achieve that goal, next-generation biogeography should ideally consider: a) dispersal-related traits; b) ecology; c) geological histories; and d) geographical factors. We briefly recap the three case studies on spiders that have pioneered this approach. Due to their old age and mega-diversity—considering both phylogenetic and life style diversity—arachnids are an ideal animal lineage for modern biogeographic research. There is no reason, however, that the concept should not be applied to all life. Further modifications of the proposed concept and, particularly, methodological implementation are needed to render this biogeographic framework widely useful.